2008
DOI: 10.1186/1475-2859-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Norvaline is accumulated after a down-shift of oxygen in Escherichia coli W3110

Abstract: Background: Norvaline is an unusual non-proteinogenic branched-chain amino acid which has been of interest especially during the early enzymological studies on regulatory mutants of the branched-chain amino acid pathway in Serratia marcescens. Only recently norvaline and other modified amino acids of the branched-chain amino acid synthesis pathway got attention again when they were found to be incorporated in minor amounts in heterologous proteins with a high leucine or methionine content. Earlier experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 34 publications
(29 reference statements)
0
60
0
Order By: Relevance
“…A possible explanation for this discrepancy is that we compared cells in stationary phase rather than exponentially growing cells growing at different rates: indeed, it has been suggested that universal stress proteins respond to reduction in growth rate [27]. In addition, regulation mechanisms of Usp-encoding genes can vary in different bacteria; for instance, gene array experiments showed anaerobic downregulation of the uspA gene in E. coli [28], consistent with its role in response to oxidative stress in this bacterium [27].…”
Section: Resultsmentioning
confidence: 93%
“…A possible explanation for this discrepancy is that we compared cells in stationary phase rather than exponentially growing cells growing at different rates: indeed, it has been suggested that universal stress proteins respond to reduction in growth rate [27]. In addition, regulation mechanisms of Usp-encoding genes can vary in different bacteria; for instance, gene array experiments showed anaerobic downregulation of the uspA gene in E. coli [28], consistent with its role in response to oxidative stress in this bacterium [27].…”
Section: Resultsmentioning
confidence: 93%
“…Since these mutants were sensitive to norvaline, it is likely they are editing defective (22). This acute sensitivity to norvaline might explain why the editing activity is maintained in most organisms, for example, when glucose-grown E. coli isolates are subjected to downshifts in oxygen tension, they produce millimolar amounts of norvaline (35). As for human pathogens, it is unclear how much selective pressure norvaline, which is a natural human metabolite (36), exerts to maintain editing function.…”
Section: Asp345mentioning
confidence: 99%
“…It may pose a significant threat to the fidelity of protein synthesis when accumulated to a concentration capable of jeopardizing the accuracy of Leu-tRNA Leu synthesis. A recent study showed that intracellular accumulation of Nva could come from the downshift of free oxygen, although free Nva is not accumulated in E. coli W3110 in aerobic cultures (47). Ross-Inta et al (48) analyzed the profiles of free amino acids and some specific derivatives in rat liver mitochondria and found that the levels of most of them (including Leu, 5.16 mM in mitochondria) were higher than in the cytosol or serum.…”
Section: Thermophilusmentioning
confidence: 99%